A soldier's place [videorecording] - Gould, Tom.; Levine, Michael. Kirk, David; Maclear, Michael; A & E Network; British Broadcasting Corporation; Canadian Broadcasting Corporation; Screenlife Incorporated (New York A%E Home Video, 1995)
A documentary on the use of United Nations Armed forces to mediate international disputes. Incorporates footage and interviews with key international policy makers.
VHS.
Host/Narrator, Major General Lewis MacKenzie.
Keywords: United Nations -- Armed Forces -- Serajerio (Bosnia); United Nations -- Armed Forces -- Cyprus; United Nations -- Armed Forces -- Somalia; Civil war; Intervention (International Law)